Twistor origin of the superstring - Berkovits, Nathan (Springer, 2015)
After introducing a d=10 pure spinor lambda(alpha), the Virasoro constraint partial derivative x(m)partial derivative x(m) = 0 can be replaced by the twistor-like constraint partial derivative x(m) (gamma(m)lambda)(alpha) = 0. Quantizing this twistor-like constraint leads to the pure spinor formalism for the superstring where the fermionic superspace variables theta(alpha) and their conjugate momenta come from the ghosts and antighosts of the twistor-like constraint.
Keywords: Superstrings and Heterotic Strings; BRST Quantization; Topological Strings